Dreams about music - analyzing the dream series of Madeline - Grams, Lea; Schredl, Michael (International journal of dream research, 2024)
Music in dreams is an interesting topic for research as it plays an important role in our daily life. In this study, we analyzed a dream series (N=926) of a female participant (pseudonym: Madeline) regarding its musical content. In summary, 10.5% dreams of the participant were music-related. This was higher compared to an unselected sample of psychology students and reflects - in line with the continuity hypothesis - the musical interests of the dreamer. While listening to music in the dream was related more often to positive emotions, playing music and singing in the dream were more negatively toned, reflecting her fear of public singing in waking life. Future in-depth studies might focus on music dreams of musicians.